2013
DOI: 10.1021/nn3036304
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Method to Quantify Nanoparticle Interaction with Lipid Bilayers

Abstract: Understanding as well as rapidly screening the interaction of nanoparticles with cell membranes is of central importance for biological applications such as drug and gene delivery. Recently, we have shown that "striped" mixed-monolayer-coated gold nanoparticles spontaneously penetrate a variety of cell membranes through a passive pathway. Here, we report an electrical approach to screen and readily quantify the interaction between nanoparticles and bilayer lipid membranes. Membrane adsorption is monitored thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
115
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(133 citation statements)
references
References 56 publications
18
115
0
Order By: Relevance
“…22 Superparamagnetic iron oxide (SPIO) and gold (Au) nanoparticles have been reported in the field of tumor disgnostics and cancer treatment. [9][10][16][17][18][19][20][21] Semiconducting nanocrystals, e.g. quantum dots, were used to improve biological imaging for medical diagnostics, 14 and these crystals were able to offer resolutions up to 1,000 times better than conventional dyes used in many biological tests.…”
Section: Nanoparticle -Membrane Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Superparamagnetic iron oxide (SPIO) and gold (Au) nanoparticles have been reported in the field of tumor disgnostics and cancer treatment. [9][10][16][17][18][19][20][21] Semiconducting nanocrystals, e.g. quantum dots, were used to improve biological imaging for medical diagnostics, 14 and these crystals were able to offer resolutions up to 1,000 times better than conventional dyes used in many biological tests.…”
Section: Nanoparticle -Membrane Interactionmentioning
confidence: 99%
“…[19][20][21][22] Inductively coupled plasma optical emission spectrometry (ICP-OES) or mass spectrometry (MS) has also been used, for example, to probe the interaction between functionalized Au nanoparticles and silica sphere-supported lipid membranes (SSLMs) by measuring the concentrations of Au nanoparticles both in the aqueous electrolytes (supernatant) and in/on the lipid bilayers. 23 The electrophysiological approach 24 coupled with the droplet-in-oil methodology has been employed to study the interaction between nanoparticles and cell membranes.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…The amphiphilic properties of the AuNPs resulted from the combination of the hydrophobic alkane backbones and the presence of a variable percentage of anionic sulphonate end groups 9 . We demonstrated that this fusion process was regulated by the size of the AuNP with a composition-dependent size threshold 24,25 . In particular, AuNPs with core diameters smaller than B3.0 nm fused independent of monolayer composition or surface structure 25 .…”
mentioning
confidence: 96%
“…Recently, using both experiments and free-energy calculations, we showed that water-soluble, amphiphilic AuNPs protected with a binary mixture of alkanethiol ligands were able to insert into and fuse with the hydrophobic core of lipid vesicles and suspended lipid bilayers 24,25 . The amphiphilic properties of the AuNPs resulted from the combination of the hydrophobic alkane backbones and the presence of a variable percentage of anionic sulphonate end groups 9 .…”
mentioning
confidence: 99%
“…With the burgeoning interest in nanoparticles, a precise understanding of their cellular uptake commands considerable current attention [24]. Given the intrinsic complexity of biological cells, several recent studies employ lipid bilayers as model systems [25][26][27][28][29][30][31][32][33][34][35][36], particularly giant unilamellar vesicles (GUVs) [37][38][39][40][41][42][43][44][45]. While many such studies demonstrate nanoparticle uptake, much of the focus has been on structural changes in the bilayer mediated by nanoparticle interactions, with some studies implicating surface charge [37,42] and others implicating hydrophobic/hydrophilic interactions [39,[43][44][45].…”
Section: Introductionmentioning
confidence: 99%